Beladikar Sebagai Inovasi Media Lagu Pendidikan Karakter Untuk Membentuk Disiplin dan Cinta Tanah Air - Hermawan, Dedy; Kusumaningsih, Widya; Nurkolis , Nurkolis (Jayapangus Press, 2025)
This study aimed to develop and evaluate Beladikar (Character Education Song Bell), a Windows-based digital application that integrates an automatic school bell with national and regional songs to strengthen elementary students’ discipline and patriotism. The research employed a Research and Development (R&D) design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with data analyzed through descriptive statistics. Expert validation indicated the application was “highly feasible,” with mean scores of 90% (content experts) and 92% (media experts). A practicality test involving 10 teachers and one school operator obtained a 91.3% positive response. Effectiveness trials with 120 students showed an average achievement of 85.5%, reflecting significant improvement in punctuality, orderly behavior, and enthusiasm in singing patriotic songs. The findings demonstrate that Beladikar not only supports time management in schools but also embeds character values consistently, thereby contributing to a positive school climate. However, the study was limited by a short trial period and restricted sample scope. Future research is recommended to involve broader educational contexts and enrich the application with interactive and mobile-based features.